OVERCOMING CHALLENGES IN SCHOOL EDUCATION MANAGEMENT - Nina Triolita; Mujahidin (Adisam Publisher, 2025)
Addressing challenges in school education management requires a comprehensive and sustainable approach. Important strategies that can be implemented include improving the competence of educators through continuous training, innovating in adaptive curriculum management and strengthening data-based monitoring and evaluation systems. Strengthening collaboration with parents and communities is also key. The holistic implementation of these strategies will ensure that schools are able to provide an educational environment that is effective and relevant to students' needs. With the support of all stakeholders, challenges in education management can be addressed more efficiently, resulting in a more meaningful and in-depth teaching and learning process, and shaping students who are ready to face the challenges of the future.